A mouse so small - McAllister, Angela; Pedler, Caroline (London : Little tiger press Ltd, 2016)
It's time for Bear's winter sleep, but he's hungry. Millie Mouse is determined not to let her friend go to bed with a rumbly tummy, so she sets off to find some food. But gathering food is hard when you're so tiny. Millie won't give up though. She may be small - but she's got a BIG heart.
Location: 3D
Keywords: Fiction book